Value generation through the implementation of the knowledge transfer 2.0 process based on the model of business Social Business (2018)
The objective of the article is identify how the intellectual capital (IC) generates value to an organization through Knowledge 2.0 Transfer Process (KTP-2.0) [12] based on the Social Business model [3]. KTP-2.0 allows the display of COOPIN 2.0 [13] that was developed in three phases, initially was to implement workshops and leisure activities with the employees of Colombian Information Technology Company, then KTP-2.0 and the COOPIN 2.0 was displayed, in which the IC was measured through indicators associated that are reflected in the formation of social networks. The participation obtained from contributions of knowledge through different agents; interactivity from the definition of communication protocols and the cooperative work supported on social media. In the results obtained, each one of the IC indicators, allow identifying the value generated to the organization, as a result of the deployment of KTP-2.0 based on the model of business set up by the social business. © 2018, revistaESPACIOS.com.